Adolescentes-mães em (dis)curso nos documentários online - ÁGATA DE CARVALHO FERREIRA (2022)
The theme of this dissertation focuses on the adolescent-mother subject constituted in online documentaries “Eu, Adolescente Mãe” (SÁ, 2008) and “Saúde no Rolê: Gravidez na Adolescence” (PLAN INTERNATIONAL, 2019). This look refers to the identity problematizations that lead the adolescent-mother subject to perform (BUTLER, 2017). The research problem is constituted in the questioning from the conditions of production, as well as its relations of knowledge, power and resistance that involve the adolescent-mother subject in the society in which he is inserted. Therefore, the hypothesis is constituted in the understanding that there is an erasure in the social roles destined to the adolescent-mother girl and an early adultization directed to her. As a general objective, it was chosen to problematize the historical and cultural performances destined to the adolescent-mother subject. The corpus consists of six excerpts from the speeches of the adolescent-mother subjects contained in the documentaries, and from them, as a first specific objective, to the interpret and track the marks of subjectivity and instabilities of the adolescent-mother subject, in relation to the devices of motherhood, work and marriage. As a second specific objective, this propose to trace the discursive formations, the inter/intradiscourses, discursive memory and archive; and, as a third objective, to discuss the relations of identity, identification and relations of knowledge, power and resistance that involve the adolescent-mother subject and the father figure. The theoretical contribution is constituted in the conflicting and transdisciplinary triad between Linguistics, History and Psychoanalysis, through the discursive-deconstructive perspective of Derrida (1995), with interpretative gestures of Coracini (2007). And so, excavate the possible genesis of discontinuities and ruptures, through Foucault's archeogenealogy (1979). From the same author, to use the notions of discourse, utterance, discursive formation, archeology and genealogy (FOUCAULT, 1987, 2002, 2015). As notions of production conditions to chose Orlandi (2004). For questions concerning the unconscious Lacan (2009). For interdiscourse, our support was given by Authier-Revuz (1998). The rely on Coracini (2007) and Lacan (1998) to work with the notions of subject. Notions of identity find support in Coracini (2015), Butler (2017) and Bauman (2005). For the purposes of meanings, to use Orlandi's thought (1988, 1996, 1999, 2007). The notion of identification is based on Lacan (2003); and, performance with Butler (2017). As a result, the adolescent-mother subject is constituted in the fragmentation of the not-one being: being a teenager, being a mother, a woman, being peripheral and resistant to power struggles and knowing that the other inscribes her. Keywords: Discourse Analysis, Adolescence, Maternity, Instabilities.